2010
DOI: 10.1007/s12650-010-0064-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the flameholding mechanisms in supersonic flows: backward-facing step and cavity flameholder

Abstract: As effective devices to extend the fuel residence time in supersonic flow and prolong the duration time for hypersonic vehicles cruising in the near-space with power, the backward-facing step and the cavity are widely employed in hypersonic airbreathing propulsive systems as flameholders. The two-dimensional coupled implicit RANS equations, the standard k-e turbulence model, and the finite-rate/eddy-dissipation reaction model have been used to generate the flow field structures in the scramjet combustors with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 77 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…The backward-facing step can generate recirculation zones with low flow velocity and prolong the residence time of the flow formed in the step corner as discussed by Halupovich et al [8], Takahashi et al [9], and Mitani and Kouchi [10]. Recently, Huang et al [11] have investigated the flameholding mechanism in the combustor. They found that the vortices formed in the corner region of the backwardfacing step and in the cavity make a large difference to the enhancement of the mixing between the fuel and the free airstream and improve the mixing and combustion efficiency in the supersonic flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The backward-facing step can generate recirculation zones with low flow velocity and prolong the residence time of the flow formed in the step corner as discussed by Halupovich et al [8], Takahashi et al [9], and Mitani and Kouchi [10]. Recently, Huang et al [11] have investigated the flameholding mechanism in the combustor. They found that the vortices formed in the corner region of the backwardfacing step and in the cavity make a large difference to the enhancement of the mixing between the fuel and the free airstream and improve the mixing and combustion efficiency in the supersonic flow.…”
Section: Introductionmentioning
confidence: 99%
“…Most of numerical investigations for the backward-facing step in supersonic flow are based on either RANS or LES [10,11,18,[24][25][26]. RANS can give the averaged parameters of the flow field and predict the large-scale fluctuations through modeling, while LES is supposed to be more accurate theoretically, provided that only the subgrid scale eddy should be modeled according to the basic hypothesis of LES that the sub-grid scale is isotropic, and the larger eddies are calculated using Navier-Stokes equations.…”
mentioning
confidence: 99%
“…The numerical approach mentioned above has been utilized successfully to analyze the flow field in cases with a cavity (Huang et al, 2011a) and with transverse injection ports (Huang, 2014). For convenience, the code validation process is not provided in this section, and readers are referred to Huang et al (2011a) and Huang (2014).…”
Section: Code Validation and Grid Independency Analysismentioning
confidence: 99%
“…For convenience, the code validation process is not provided in this section, and readers are referred to Huang et al (2011a) and Huang (2014). A comparison between numerical results and published experimental data, as well as the grid independency analysis, has been provided by Huang et al (2011a) and Huang (2014). Fig.…”
Section: Code Validation and Grid Independency Analysismentioning
confidence: 99%
“…Therefore, the waverider is a good candidate for hypersonic flight [4]- [10]. Nowadays, there have been some remarkable vehicles which are designed based on waverider configuration, such as X-51A [11] and HTV-2.…”
Section: Introductionmentioning
confidence: 99%